2020
DOI: 10.1038/s41598-020-61932-0
|View full text |Cite
|
Sign up to set email alerts
|

Low FVC/TLC in Preserved Ratio Impaired Spirometry (PRISm) is associated with features of and progression to obstructive lung disease

Abstract: One quarter of individuals with Preserved Ratio Impaired Spirometry (PRISm) will develop airflow obstruction, but there are no established methods to identify these individuals. We examined the utility of FVC/TLC in identifying features of obstructive lung disease. The ratio of post-bronchodilator FVC and tLc ct from chest ct (fVc/tLc ct) among current and former smokers with pRiSm (feV 1 /fVc ≥ 0.7 and FEV1 < 80%) in COPDGene was used to stratify subjects into quartiles: very high, high, low, and very low. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 47 publications
3
27
0
1
Order By: Relevance
“…Healthcare practitioners also should recognize that while 17–24% of patients with preserved lung function may not fulfill the spirometry criterion for a diagnosis of COPD [ 39 ], they may nonetheless experience respiratory symptoms, exacerbation-like events, and activity limitations with some evidence of airway disease [ 40 ]. Notably, a subset of patients with preserved ratio impaired spirometry (PRISm) eventually progress to meet the spirometric criterion for COPD and are at increased risk of respiratory symptoms, respiratory exacerbations, and mortality [ 41 43 ]. Currently, however, GOLD recommendations do not address the therapeutic management of patients with PRISm, who represent a heterogenous population, that is possibly underdiagnosed and underappreciated.…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare practitioners also should recognize that while 17–24% of patients with preserved lung function may not fulfill the spirometry criterion for a diagnosis of COPD [ 39 ], they may nonetheless experience respiratory symptoms, exacerbation-like events, and activity limitations with some evidence of airway disease [ 40 ]. Notably, a subset of patients with preserved ratio impaired spirometry (PRISm) eventually progress to meet the spirometric criterion for COPD and are at increased risk of respiratory symptoms, respiratory exacerbations, and mortality [ 41 43 ]. Currently, however, GOLD recommendations do not address the therapeutic management of patients with PRISm, who represent a heterogenous population, that is possibly underdiagnosed and underappreciated.…”
Section: Resultsmentioning
confidence: 99%
“…4,40,41 Air trapping based on radiographic lung volumes predicts accelerated spirometry decline and progression to COPD in smokers without obstruction. 4,33,40,41 Based on the above, we conclude that FEV 1 to SVC ratio can be a simple, routinely available spirometric index that can identify individuals who may benefit from early intervention such as smoking cessation. Confirmation of obstructive lung disease by an objective measurement like FEV 1 to SVC ratio may motivate smokers to quit smoking, 42,43 which is the only proven intervention that can modify disease progression.…”
Section: Q34mentioning
confidence: 80%
“…In individuals with mild obstructive lung disease, this phenomenon may result in pseudonormalization of the FEV 1 to FVC ratio, whereas in those with substantial obstructive lung disease, it may result in preserved ratio impaired spirometry results. [32][33][34] Using the FEV 1 to SVC ratio instead of the FEV 1 to FVC ratio results in an increase in the reported prevalence of COPD 35,36 and may lead to overdiagnosis, in particular among elderly individuals. 7 Nevertheless, in the absence of a true gold standard for COPD diagnosis, the usefulness of a diagnostic test is related highly to its association with the clinical, functional, and radiographic features of a disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported prevalence rates for PRISm as between 12 and 24% [1][2][3][4] . In this study, the prevalence rate was 12.0%, which was similar to that reported in some other countries.…”
Section: Discussionmentioning
confidence: 99%